THYMINELESS DEATH IN BACILLUS MEGATERIUM - Wachsman, J. T. (1964)
Wachsman, J. T. (University of Illinois, Urbana), S. Kemp, and L. Hogg. Thymineless death in Bacillus megaterium. J. Bacteriol. 87:1079–1086. 1964.—Strain KM:T(−), a thymine auxotroph of Bacillus megaterium strain KM, rapidly loses the ability to multiply when incubated in the absence of thymine, on an otherwise sufficient medium. At 37 C, there is a lag of approximately 60 min, prior to the onset of exponential death (decrease of 1 decade per 50 min). The extent of the decrease in viable count varies from 4 to 5 decades after 5 hr of starvation. The cells die more slowly at 30 C (decrease of 1 decade per 120 min) after a lag of approximately 90 min. Thymine starvation permits substantial net ribonucleic acid (RNA) and protein synthesis, but only slight deoxyribonucleic acid synthesis. In contrast with the changes occurring at 30 C, thymineless death at 37 C is eventually accompanied by a rapid hydrolysis of RNA and by cell lysis. Chloramphenicol inhibits thymineless death at 37 C. Strain T(−)R(1), a derivative of strain KM:T(−), undergoes a very low rate of thymineless death at 37 C (decrease of 1 decade per 240 min). Neither hydrolysis of RNA nor cell lysis occurs during 8 hr of thymine starvation. Strain KM:T(−)H(−) (doubly auxotrophic for thymidine and histidine) requires histidine for maximal thymineless death at 37 C. Preincubation of this strain on the basal medium supplemented with thymidine alone enables the population to become increasingly immune to subsequent thymineless death.